2023
DOI: 10.1186/s12879-023-08262-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of presepsin and Mid-regional pro-adrenomedullin in the diagnosis of sepsis or septic shock: a systematic review and meta-analysis

Abstract: Background The early diagnosis of sepsis is hampered by the lack of reliable laboratory measures. There is growing evidence that presepsin and Mid-regional pro-adrenomedullin (MR-proADM) are promising biomarkers in the diagnosis of sepsis. This study was conducted to evaluate and compare the diagnostic value of MR-proADM and presepsin in sepsis patients. Methods We searched Web of Science, PubMed, Embase, China national knowledge infrastructure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…These findings are consistent with the results of a recent meta-analysis centered on the diagnostic capability of presepsin for sepsis, wherein the cutoff values spanned from 89.26 to 1,315 pg/mL. The extensive variation in these cutoff values could be attributed to disparities in disease severity, study methodologies, and clinical settings ( 13 ). To determine a clinically relevant cutoff value, further research targeting specific patient subgroups and the efficacy of presepsin is essential.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These findings are consistent with the results of a recent meta-analysis centered on the diagnostic capability of presepsin for sepsis, wherein the cutoff values spanned from 89.26 to 1,315 pg/mL. The extensive variation in these cutoff values could be attributed to disparities in disease severity, study methodologies, and clinical settings ( 13 ). To determine a clinically relevant cutoff value, further research targeting specific patient subgroups and the efficacy of presepsin is essential.…”
Section: Discussionsupporting
confidence: 88%
“…While previous studies reported elevated presepsin levels in patients with viral meningitis and fungemia ( 37 , 38 ), the diagnostic accuracy for sepsis related to parasites, viruses, and fungi remains to be firmly established. During the onset of sepsis, the levels of presepsin elevate early ( 39 , 40 ), making it a valuable indicator for detecting and predicting the course of sepsis ( 13 ). While surgical trauma has not been associated with elevated presepsin levels ( 1 , 15 , 22 ), the utility of presepsin in the diagnosis of PICs remain unclear due to the lack of consolidated evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The area under the curve (AUC) was 0.89 (95% CI: 0.86-0.92) [123]. Presepsin and MR-proADM have shown good values of accuracy in another meta-analysis by Liang et al [124].…”
mentioning
confidence: 93%